A case study on Telekom Sales & Services Sdn Bhd - Mohd Roslan bin Haron (2010)
Telecommunicati0n is fast turning into a necessity. Nowadays, even a school going children has a mobile phone. It is difficult to find a ~eenager without a hand phone. Some adults even have more than one mobile phone, each caters for different purpose. The usage of telecommunication also shifted from voice to connectivity. Internet has definitely changed the way people live. Previously, the phone line that we have at home is only for voice but now with triple play technology we can talk, browse Internet and watch movie at the same time. With so many devices in the market, customers are spoilt for choice. Low price and excellent after sales service would be the preferred criteria for choosing the right equipment. Customer is king. Therefore, company must provide supreme customer services to attract and retain customers. Telekom Malaysia, through its subsidiary Telekom Sales & Services Sdn Bhd, takes customer service seriously. Every customer that interfaces with its touch points is treated with utmost importance. TMpoint, one of its touch points, even has a specific measurement on customer service that covers on product, process, people and positioning. The customer service starts from customer inquiry for a certain product. Then, the application process of acquiring the service is expected to be efficient. Most importantly is the speed it takes to process the application and activate the service so that customer can actually start using the service. Customer service also touches on accuracy of the billing and after sales support. Therefore, customer service is from a potential customer until the customer becomes a loyal customer. The customer experience plays a very important aspect ofTelekom Malaysia, and Telekom Sales & Services Sdn Bhd, operation. Complaints from customer are always related with customer service. From the finding derived from the Rapid Response Team Analysis 2009 Report, a total of3,720 complaints received by TM from customers. TMpoint contribute 12% of the total point of failure (PoF). SWOT Analysis showed that competent staff is one of the strength ofTM and TSSSB and yet customer complaints still exist. Could it be other than people issue? TOWS Matrix is used to plan for alternative strategies, which can be used as a tactical tool too. Specific strategy can be followed based on the TOWS Matrix analysis by zooming at specific area of concern. The finding shows that the process, or rather the lack of it, is where the problem is. Product development is the way to go forward. TM is a strong company, financially. The Financial Analysis done verified that TM is able to fulfil financial obligation with ease. What about their performance in the industry? The analysis will show that even though TM is financially strong but in term of profitability, it may not be the top, in a very high capital expenditure industry. But with financial might, TM and TSSSB can address customer service issues by embracing IT. With centralised single system, as proposed in the paper, front liners would be able to increase customer satisfaction.